2020
DOI: 10.3390/nano10081446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varying Amine Functionalities on CO2 Capture of Carboxylated Graphene Oxide-Based Cryogels

Abstract: Graphene cryogels synthesis is reported by amine modification of carboxylated graphene oxide via aqueous carbodiimide chemistry. The effect of the amine type on the formation of the cryogels and their properties is presented. In this respect, ethylenediamine (EDA), diethylenetriamine (DETA), triethylenetetramine (TETA), were selected. The obtained cryogels were characterized by Fourier Transformed Infrared spectroscopy, thermogravimetric analysis, X-ray spectroscopy, and Scanning electron microscopy. The CO2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 80 publications
(116 reference statements)
3
16
0
Order By: Relevance
“…The selectivity for CO 2 over N 2 increased in the same trend, from 11 to 21 and 38 for the modified aerogels with 0.2 mg mL −1 G7, 0.2 mg mL −1 G3, and 0.1 mg mL −1 G7, respectively. These results indicate the adsorption performance was not only affected by pore characteristics, but also by N content in terms of N/C ratio and nitrogen binding contributions to total nitrogen content, as indicated in recent literature [7,8,10,52].…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…The selectivity for CO 2 over N 2 increased in the same trend, from 11 to 21 and 38 for the modified aerogels with 0.2 mg mL −1 G7, 0.2 mg mL −1 G3, and 0.1 mg mL −1 G7, respectively. These results indicate the adsorption performance was not only affected by pore characteristics, but also by N content in terms of N/C ratio and nitrogen binding contributions to total nitrogen content, as indicated in recent literature [7,8,10,52].…”
Section: Methodssupporting
confidence: 78%
“…The three-dimensional (3D) porous aerogels obtained from reduced graphene oxide (rGO) are considered promising sorbents for CO 2 capture given their low density, interconnected porous network, large surface area, and active sites, which in turn are dependent on the synthesis route [5,6]. A two-step method based on simultaneous solvothermal reduction and self-assembly of GO and a subsequent freeze-drying procedure has been shown as a convenient approach for fabricating 3D GO-based aerogels [5,[7][8][9][10][11][12][13]. Varying solvothermal conditions have been studied for the gelation and self-assembly of GO, such as temperature, duration, GO concentration, or GO flake size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the modification reactions are based on the introduction of the N in the structure. Some of these examples are based on ethylenediamine, diethylenetriamine, triethylenetetramine (showing CO 2 adsorption of 2.0 mmol/g at 1 bar and 298 K [18], with urea (CO 2 adsorption at atmospheric pressure, and 25 • C of 2.40 mmol/g) [19], with hydrazine during reduction (for supercapacitors) [20] and ethylenediamine (1.1 mmol/g of CO 2 adsorption) [21]. Some other works involve doping with S, P, and N grown with Co 9 S 8 nanoparticles (as a bifunctional catalyst) [22] or silylation by employing three distinct silica precursors (CO 2 adsorption of 3.5 mmol/g at 5 bar and 0 • C [23] or thiolene click reaction [24].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, other works can be found by using MgO, rGO, and amorphous carbon to prepare sandwich-like structures (CO 2 adsorption up to 31.5 wt % at 27 • C, 1 bar CO 2 22.5 wt % under the simulated flue gas) [25]. In most of these works it was concluded that the functionalization of 3D rGO materials by introducing various heteroatoms functional groups is a useful tool to improve the textural properties (porosity and SA) [18,19,23,25], CO 2 capture capacity [18,19,21,23,25] and/or selectivity over N 2 [19,21].…”
Section: Introductionmentioning
confidence: 99%